Spatial Analysis of Leading Tourism Areas in East West Sumatra Province - Silvia Clori; Rika Despica (Universitas Pahlawan Tuanku Tambusai, 2023)
The background of this research is that each region in West Sumatra already has a leading tourist area, but there is no boundary determining the Leading Tourism Area for Eastern Part of West Sumatra, but there are no exact (real) numbers in which areas are the next destination after the initial leading tourist destination. the tourists.This study uses the Quantitative Descriptive analysis method. The population of this research is tourism objects in the eastern part of West Sumatra including Solok City, Sawahlunto City, Sijunjung Regency, Dhamasraya Regency and Solok Regency. The sample of this study consisted of the Eastern Part of the Leading Tourism Area of ??West Sumatra, using field observation data collection techniques and how to take coordinates in the leading tourist areas.The results of this study show the characteristics of leading tourist areas in the form of topography, road networks, rivers, and morphology. The establishment of leading tourist areas depends on the topography of the region. The eastern part of West Sumatra has its own superior tourist area which has been determined by the Governor of West Sumatra. There are 2 patterns of distribution of leading tourist destinations in eastern West Sumatra, namely Solok City, Sawahlunto City, Dhamasraya Regency, and Solok Regency which are uneven or random (patern), and Sijunjung Regency which is evenly distributed or regular (different pattern or regular)